Seventeenth-Century Metallurgy on the Spanish Colonial Frontier : Pueblo and Spanish Interactions. - Thomas, Noah H. (Anthropological papers (Vermillion, S.D.), 2018)
"A critical analysis of archaeological features and materials related to metal production excavated from the early colonial period (AD 1598-1680) of the Pueblo of Paa-ko (LA 162) in Bernalillo County, New Mexico"--Provided by publisher.